Share fairs - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
These are interactive events that employ various knowledge sharing formats such as market stalls and booths, and workshops and presentations designed to encourage discussions.